A case report of pudendal arteries angioplasty with sirolimus drug-coated balloon and drug-eluting stent associated with intracavernous autologous peripheral blood mononuclear cells injection for untreatable vasculogenic erectile dysfunction. Issue 8 (15th August 2021) - Terlizzese, Giuseppe; Stubinski, Robert; Casini, Andrea; Clerici, Giacomo; Sangiorgi, Giuseppe
Abstract: Background: Erectile dysfunction (ED) is a prevalent health problem that seriously impacts men's quality of life. The potential treatment of ED by percutaneous approach has emerged with valid angiographic results and a significant improvement in symptoms and quality of life. In addition, cell-based regenerative therapies aiming at enhancing neovascularization have been successfully performed with peripheral blood mononuclear cells (PBMNCs) in diabetic patients affected by critical limb ischaemia. Case summary: We report a case of a young insulin dependent (ID) diabetic patients who suffered of severe vasculogenic erectile dysfunction associated with a poor response for more than 1 year to oral phosphodiesterase-5 inhibitors (PDE5i) and intracavernous (IC) phosphodiesterase type 1 (PDE1) therapy. At selective angiography of the pelvic district, a severe atherosclerotic disease of the internal iliac and pudendal artery was evident with absence of distal vascularization of the cavernous bodies. The patient was treated by mechanical revascularization with drug-coated balloon and drug-eluting stent placement associated with IC injection of autologous PBMNCs. Immediate and 1-year clinical and angiographic follow-up are described. Discussion: Percutaneous revascularization with drug-coated balloon and drug-eluting stent associated with IC autologous PBMNCs cells injection is a safe and effective procedure to restore normal erectile function in diabetic patients affected by severe vasculogenic ED not responding to conventional oral drug therapies.